2017
DOI: 10.1038/s41598-017-01491-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydration effects on the efficacy of the Epidermal growth factor receptor kinase inhibitor afatinib

Abstract: Small molecules targeting the EGFR tyrosine kinase domain have been used with some success at treating patients with non-small cell lung cancer driven by activating mutations in the kinase domain. The initial class of inhibitors displaced ATP noncovalently but were rendered ineffective due to the development of resistance mutations in the kinase domain. These were overcome by the development of covalent inhibitors such as afatinib which also bind in the ATP pocket. However pooled analysis of two recent clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…Our data indicate that EGFR G724S mutations seem to primarily affect the reversible first step of third-generation inhibitor binding within the ATP-binding pocket before irreversible attachment to Cys797 can occur. We conclude that the observed fluctuation of the glycine-rich loop plays a role in this phenotype, similar to other systems where anti-correlations between flexibility and ligand-binding affinity have been observed 49 , 50 . However, although the kinetics of third-generation EGFR inhibitor binding are perturbed dramatically, second-generation EGFR inhibitors are potent enough to establish such a reversible binding despite the EGF R G724S mutation.…”
Section: Discussionsupporting
confidence: 87%
“…Our data indicate that EGFR G724S mutations seem to primarily affect the reversible first step of third-generation inhibitor binding within the ATP-binding pocket before irreversible attachment to Cys797 can occur. We conclude that the observed fluctuation of the glycine-rich loop plays a role in this phenotype, similar to other systems where anti-correlations between flexibility and ligand-binding affinity have been observed 49 , 50 . However, although the kinetics of third-generation EGFR inhibitor binding are perturbed dramatically, second-generation EGFR inhibitors are potent enough to establish such a reversible binding despite the EGF R G724S mutation.…”
Section: Discussionsupporting
confidence: 87%
“…Increased flexibility and destabilization of the αC-helix have also been reported in earlier computational studies. 14 20 This clearly points to the structural requirement of a helical motif in this region (the short helix) to stabilize the kinase in its inactive state. Apart from the increased flexibility observed for the A-loop, the αC-helix and the P-loop (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The T790M mutation is thought to stabilize the active form of the kinase by stabilizing the hydrophobic spine, 12 , 13 while the L858R mutation is known to destabilize the inactive form and stabilize the kinase in an intermediate form. 14 20 We therefore subjected our models of the T790M, L858R and L858R/T790M mutants in their inactive states to multiple μs MD simulations. The simulations very quickly show that the L858R substitution, either as a single point mutation or in combination with T790M, is not tolerated as modelled based on the wild type conformation, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MD studies on other recurring mutations such as R776H in the αC-β4 loop have identified novel autoinhibitory interactions associated with kinase activation (25) and protonation-dependent changes in mutant EGFR functions (30). In addition, MD-based free-energy methods (26,31), molecular mechanics calculations (32), and molecular modeling studies (33) have provided new insights into mutation-induced drug resistance mechanisms and the conformational transitions connecting active and inactive states (34)(35)(36).…”
Section: Significancementioning
confidence: 99%